2007
DOI: 10.1021/jm0706822
|View full text |Cite
|
Sign up to set email alerts
|

Conformation−Activity Relationship of Neuropeptide S and Some Structural Mutants:  Helicity Affects Their Interaction with the Receptor

Abstract: Neuropeptide S (NPS) is the endogenous ligand of the previously orphan G-protein coupled receptor now named NPSR. The NPS-NPSR receptor system regulates important biological functions such as sleep/waking, locomotion, anxiety and food intake. Recently, exhaustive Ala scan and d-amino acid scan studies, together with systematic N- and C-terminal truncation, led to the identification of key residues for biological activity. Because conformational preferences might also play an important role, we undertook a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 48 publications
5
29
2
Order By: Relevance
“…NPS conformational investigations performed by NMR experiments indicated that NPS presents a completely disordered conformation in water. 64 However, several NH-NH cross peaks were observed by Bernier et al 57 in the NPS region 5-13; this lead these authors to hypothesize the presence of a nascent helix in this region, which, during the NPSR binding process, may favor the formation of a stable a helix structure.…”
Section: Npsr Peptide Ligandsmentioning
confidence: 97%
See 3 more Smart Citations
“…NPS conformational investigations performed by NMR experiments indicated that NPS presents a completely disordered conformation in water. 64 However, several NH-NH cross peaks were observed by Bernier et al 57 in the NPS region 5-13; this lead these authors to hypothesize the presence of a nascent helix in this region, which, during the NPSR binding process, may favor the formation of a stable a helix structure.…”
Section: Npsr Peptide Ligandsmentioning
confidence: 97%
“…In fact, both substitutions generated peptide derivatives that showed only slightly reduced potency compared to NPS. 64 This suggests that an a helix conformation (favored by L-Ala but not by D-Ala) is, at least in this portion of the NPS sequence, not important for NPSR binding. Interestingly, [D-Ala 5 ]NPS behaves as a partial agonist at NPSR with efficacy corresponding to half of that of NPS.…”
Section: Npsr Peptide Ligandsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, a series of structure-activity relationship studies have been carried out for the neuropeptide, and some examples of NPS analogues with partial agonist or even antagonist profiles have been reported recently. [18][19][20][21][22][23] More limited information is available about nonpeptide NPSR antagonists, as only one series of bicyclic piperazine derivatives has been published in this regard. [24][25][26] These molecules (Table 1) present NPSR antagonist potencies with K e values from the low nanomolar range to the micromolar level, with non-identical profiles when tested at NPSR-A and NPSR Ile 107.…”
Section: Introductionmentioning
confidence: 99%